Sejarah Pondok Pesantren al-Falah Gedongan, Baki, Sukoharjo, Jawa Tengah (2006-2018) - Adib Abbiya Qowiyyuddin (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2022)
Pesantren is an Islamic subculture rooted in Islamic culture in Indonesia. Education in pesantren is not only synonymous with educational facilities and practices but also the inculcation of a number of moral values and characters. The establishment of the Al Falah Islamic Boarding School had a socio-religious impact on the community and became a  centre for Islamic studies in the Gedongan area, Baki, Sukoharjo. The approach used by researchers in cultural sociology. The Cultural Sociology approach examines the concepts and behaviour of people who are able to interpret and solve cultural phenomena from a sociological point of view. The theory used in this research is the structural-functional theory proposed by Robert K Merton. The method used is the historical method, which includes four steps, namely heuristics, verification, interpretation and historiography.